Godt nyt fra Afrika: bønder, landbrugsforskning of mad på bordet - Schioler, Ebbe (Udenrigsministeriets Informationssekreariat. Danida., 1998)
This book touches only briefly on the actual research process. Instead, it concentrates on describing some of the countless research breakthroughs that are helping farmers in Africa get more out of their land. ... Behind each breakthrough lies one of the international centers for agricultural research ... But it is the small farmers who have shown, in practice, that all of the researchers' hard work is worthwhile. And that practical testing, out there on the farmers' own small plots, is what this book is about, because it is there that the value of the research is put to the ultimate test.